This taste for silence - O'Callaghan, Amanda (UQP Short Fiction Ser., 2019)
The balance of power in a marriage shifts, with shocking consequences. An elderly woman recounts a chilling childhood memory on the family farm. A taxi driver with a missing wife reveals unexpected skills. An inherited painting brings an eerily troubling legacy. Subtle, compelling and unsettling, Amanda O'Callaghan's stories work at the edges of the sayable, through secrets, erasures and glimpsed moments of disclosure. They shimmer with unspoken histories and characters who have a taste for silence'